I Wayan Ary Wijaya's Creative Process in Creating Digital Gamelan Music - Kadek Wahyudita; I Komang Sudirga; I Wayan Suharta (Journal of Aesthetics, Creativity and Art Management, 2022)
This paper is to trace the creative process in composing Digital Gamelan Music (DGM) done by I Wayan Ary Wijaya a balinese artist. It a qualitative study by operating observation, documentation, and interview. Interview is done with I Wayan Arsa Wijaya and other related parties. DGM was created by Ary Wijaya from linking gamelan and music technology. DGM is another way to strengthen tradition and at the same time foster creativity by using the gamelan (traditionality) and the technology (modernity) as a medium of inspiration. It is found that DGM is composed using Panca Sthiti Ngawi Sani theory: inspiration stage (ngawirasa); exploration stage (ngawacak); conception stage (ngarencana); execution stage (ngewangun); presentation stage (ngebah). DGM as a terminology is still experiencing struggles in terms of concept definition, form, and creative work process. Besides that, the digital technology belongs to a product of capitalism.